The design of preferential trade agreements: A new dataset in the Making - Leonardo Baccini; Andreas Dür; Manfred Elsig; Karolina Milewicz (World Trade Organization (WTO), 2011)
Since 1990 the number of preferential trade agreements (PTAs) has increased very rapidly. This paper aims to contribute to this literature by presenting a new database on PTAs called Design of Trade Agreements (DESTA). We identified a total of 690 negotiated trade agreements between 1945 and 2009 of which we have coded 404 agreements for which treaty texts and appendices were available. We aim to have a database for about 550 agreements by 2012. We have coded agreements for a total of 10 broad sectors of cooperation, encompassing market access, services, investments, intellectual property rights, competition, public procurement, standards, trade remedies, non-trade issues, and dispute settlement. For each of these sectors, we have coded a significant number of items, meaning that we have about 100 data points for each agreement. The resulting DESTA database is to the best of our knowledge by far the most complete in terms of agreements and sectors covered. This dataset fills a crucial gap in the field by providing a fine-grain measurement of the design of PTAs. Among others, we think that DESTA will be of relevance for the literatures on the signing of PTAs; the legalization of international relations; the rational design of international institutions; the diffusion of policies; the political and economic effects of trade agreements; power relations between states; and forum shopping in international politics. This working paper describes the DESTA data set and provides selected descriptive statistics. The overview puts emphasis on variation in design over time and across regions.
Keywords: F15; 330; preferential trade agreements; Außenhandelspräferenz